2016
DOI: 10.1097/md.0000000000005601
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-TKIs versus taxanes agents in therapy for nonsmall-cell lung cancer patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…[ 2 ] The epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) gefitinib and erlotinib are part of a new treatment strategy for NSCLC patients with EGFR mutations and have improved the progression-free survival (PFS), overall survival (OS), and quality of life in patients compared to traditional platinum-based combination chemotherapy. [ 3 6 ] Epidermal growth factor receptor (EGFR) gene-activating mutations are strong predictive factors of response and survival to EGFR-TKIs. [ 7 , 8 ] It is generally accepted that 2 classical mutations (exon 19-del and exon 21-L858R) can enhance the sensitivity of tumor cells to EGFR-TKIs and are considered to be an effective predictor of the efficacy of EGFR-TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] The epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) gefitinib and erlotinib are part of a new treatment strategy for NSCLC patients with EGFR mutations and have improved the progression-free survival (PFS), overall survival (OS), and quality of life in patients compared to traditional platinum-based combination chemotherapy. [ 3 6 ] Epidermal growth factor receptor (EGFR) gene-activating mutations are strong predictive factors of response and survival to EGFR-TKIs. [ 7 , 8 ] It is generally accepted that 2 classical mutations (exon 19-del and exon 21-L858R) can enhance the sensitivity of tumor cells to EGFR-TKIs and are considered to be an effective predictor of the efficacy of EGFR-TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from histological studies, some researchers have focused on genetic mutations, whose results were controversial. The mutations of epidermal growth factor receptor (EGFR) are an indicator in targeted therapy of non-small cell lung cancer (NSCLC) [32]. Yip et al used MATLAB software and first reported 8 novel PET radiomic signatures, which helped to predict EGFR mutations of NSCLC in 348 patients successfully.…”
Section: Genetic Statusmentioning
confidence: 99%
“…New targets continue to emerge, such as BRAF mutations (dabrafenib and trametinib) or the ROS1-gene targeted by crizotinib. Numerous meta-analyses have investigated the expected benefits for patients managed with these treatments showing significant gains in progressionfree survival [21][22][23][24][25][26][27] and impact on OS being currently investigated. For our study, the 4-month gain in median survival delivered by the 10 new therapies over four decades (and 28 more used off-label) seems low when compared with the threshold of at least a 3.25-to 4-month gain as a measure of meaningful improvement of a new therapy over standard of care recommended by the American Society of Clinical Oncology (ASCO) [28].…”
Section: Plos Onementioning
confidence: 99%